PWE-139 Outcome of liver resection for non-colorectal and non-neuroendocrine liver metastases (NCRNNE). (28th May 2012) - Dave, R; Cockbain, A; Hidalgo, E; Prasad, R; Lodge, P; Toogood, G
Abstract : Introduction: The liver is a frequent site for tumour metastases, and surgery for colorectal liver metastases (CRLM) is well established, with survival rates accepted to be 50% in 5 years. However, surgery for NCRNNE has been approached with caution. We aimed to report the outcomes of surgery for NCRNNE in our unit, to determine the patterns of disease presentation, recurrence and survival. Methods: We identified 78 patients who had liver resection from NCRCNNE primary tumours from 28 December 1992 to 2 August 2011 using a prospectively maintained database; Breast (N=19), Malignant Melanoma (N=4), Renal (N=10), Anal Squamous Cell Carcinoma (N=5), Lung (N=3), Sarcoma (N=15), GIST (N=13), Squamous-other (cervix, bile duct, oropharynx) (N=6) and Gastric Adenocarcinoma (N=3). The electronic records of all these patients were then retrospectively reviewed. We obtained data on patient demographics, presentation of disease, pathological data, recurrence and survival. Data were analysed using ANOVA and Kaplan–Meier tests. Results: The age at diagnosis varied with tumour type; the youngest was sarcoma (46 years) and the oldest gastric (67 years). The progression to detectable liver disease was quickest with Anal Squamous Cell Carcinoma metastases (172 days), which also had a 60% recurrence rate within a mean of 192 days. Malignant Melanomas had a 100% recurrence rate, which occurred at a mean of 321 days. Breast metastases were the least likely to recur (33%) and had a long disease-free period between recurrences (468 days). The largest metastases were seen in sarcomas (67 cm) and the smallest in melanomas (28 cm). There was no significant correlation between size or number of tumours and survival. The 1- 3- and 5-year survival from the time of NCRCNNE metastectomy was 88%, 56% and 47% respectively, compared with 86%, 58% and 46% after CRLM metastectomy. Malignant Melanomas and Anal Squamous Cell Carcinoma had the poorest outcome; 100% mortality at 5 years. Conclusion: Liver Resection is an effective treatment for metastases from NCRCNNE tumours in highly selective patients. In the right patient, surgery offers similar survival rates to resection of CRC metastases, but some tumour types do better than others, and a decision to proceed with resection should take into account the histological diagnosis, and an understanding of the behaviour of that tumour type. Competing interests: None declared.